Situational analysis of the agriculture sector nationally determined contribution (NDC) in Kenya - African Group Of Negotiators Experts Support (AGNES) (International Livestock Research Institute, 2024)
The agricultural sector serves as the cornerstone of the Kenyan economy, wielding significant economic influence by directly contributing 33% of the Gross Domestic Product (GDP), and another 27% of the GDP indirectly through linkages with other sectors (FAO, 2025). The sector accounts for 65% of total export earnings and sustains informal livelihoods of more than 80% of the Kenyan population in meeting employment, income and food security needs and contributes to improving nutrition through production of safe, diverse and nutrient dense foods. The sector also employs over 40% of the total population and more than 70% of the rural population (Central Bank of Kenya, 2023; World Bank Group 2021). The sector is also the main driver of the non-agricultural economy including manufacturing, providing inputs and markets for non-agricultural operations such as building or construction, transportation, tourism, education and other social services. This underscores the pivotal role of the agricultural sector in driving Kenya’s economy and providing livelihoods for a substantial portion of the population. Climate change poses significant threat to the Kenyan economy due to its dependence on natural resources such as water for food and energy, and the country’s exposure to climate-sensitive sectors, especially agriculture. The rising frequency of extreme weather events is the main driver of climate change-related impact on the Kenyan economy. Kenya’s agricultural sector is heavily reliant on rain-fed smallholder subsistence farming, which exposes the sector to profound impacts of climate change. Increasing variability of rainfall patterns, increasing temperature interspersed with prolonged drought periods and flash floods directly affecting crop and livestock productivity. This impact is varied across the country with higher temperatures having a positive impact in highland areas but a negative effect in lowland areas, with this being pronounced in the ASAL regions. Smallholder farmers who make up majority of Kenyan farmers, are highly vulnerable to climatic and environmental hazards as their options for diversifying their resources and income sources are limited. Droughts negatively affect access to credit for agriculture, as the value and availability of farm assets to serve as collateral decline. Further, their vulnerability is worsened by lack of access to adequate water, low levels of technology and education and institutional mismanagement. These challenges exacerbate the vulnerability and dampen adaptive capacity of smallholder farmers to climate shocks, particularly in the food basket regions.